The Allelopathic Potential of Ruderal Plant Species on Tomato and Lettuce - Marija Ravlić; Renata Baličević; Željka Vinković; Bojana Brozović; Ankica Sarajić; David Kranjac (Poljoprivreda)
The aim of the study was to evaluate the allelopathic potential of several ruderal plant species on the germination and initial growth of tomato and lettuce. The water extracts from dry aboveground biomass in a five-percent concentration were evaluated under the controlled laboratory conditions in a Petri dish bioassay. The research findings indicated that all species exhibited the allelopathic effects and were ranked by their average inhibitory potential, from the highest to the lowest, as follows: Melilotus albus, Portulaca oleracea, Verbascum phlomoides, Plantago lanceolata, Cichorium intybus, Rorippa austriaca, Vicia grandiflora, Eupatorium cannabinum, and Polygonum aviculare, respectively. A water extract of M. albus had the most significant negative impact, causing an average reduction of 43.9% in germination, 93% in the root length, and 89.4% in the shoot length. Conversely, a water extract of P. oleracea showed a notable stimulatory effect on both test species. The pH value of water extracts from the ruderal plant species ranged from 5.26 (P. aviculare) to 7.71 (V. grandiflora and M. albus) and did not influence their negative allelopathic potential.